PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN METODE PEMBERIAN LEMBAR TUGAS SISWA PADA MATERI EKOSISTIM SISWA KELAS VII 2 SMP NEGERI 2 DUMAI - Sajarotunnur ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aims to improve student learning outcomes by applying the method VII.2 classassignment sheet giving students conducted in March and April 2016. Subjects were seventhgrade students of SMP Negeri 2 Dumai totaling 26 students. The parameters in this study isthe absorption and mastery learning as well as student activities and teacher activities assupporting data. The research instrument used is the study and data collection instruments.The device consists of a learning syllabus, lesson plan, test, observation of student activitysheets, activity sheets teacher observation. The survey results revealed absorption of studentsin the first cycle is 70% with moderate category and second cycle increased to 78% in thehigh category. Mastery learning of students in the first cycle is 88.46% and 88.50% in thesecond cycle students completed. Activities of students in the first cycle an average of80.76%% (very good) and the second cycle is an increase of 97.5% (excellent). It can beconcluded that the method of administration of the student assignment sheet can improvestudent learning outcomes in the classroom ecosystem VII 2 material SMP Negeri 2 Dumai.